Applying Zone of Tolerance to a Customer Service App in a Public Higher Education Institution - Abrar Erlangga, Alif Muhammad; Perdanakusuma, Andi Reza; Hariyanti, Uun (Journal The Winners, 2025)
Rapid technological evolution has compelled many higher education institutions to adopt digital-based customer service systems to improve efficiency and productivity. At the same time, service quality in higher education institutions influences credibility and competitiveness in the sector. Therefore, an evaluation of a web-based customer service platform at a university in Malang is necessary. This research aims to evaluate the service quality of this platform from a user perspective and identify priority areas for improvement using the Zone of Tolerance (ZOT) framework. This research applied a mixed-method design. The population consisted of 1,506 students from 2021 to 2023, and the sample consisted of 102 respondents, obtained through questionnaires and one interview. Quantitative analysis measured desired, adequate, and perceived services using the DeLone and McLean model, while qualitative analysis applied thematic analysis to enrich the findings. Results show that no indicators fall below the ZOT, 13 indicators are within it, and one exceeds user expectations. This research is novel in applying the ZOT for the first time to evaluate an online customer service platform in higher education and in using the DeLone and McLean model rather than the commonly applied SERVQUAL instrument. The findings provide insights for improving service quality and enhancing user satisfaction.